Implementation of the UCD (User Centered Design) Method for monitoring the Implementation of Personnel Tasks at DITSAMAPTA Website Based Police of North Sumatra - Eka Rahayu; Arie Rafika Dewi (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
DITSAMAPTA Polda Utara Sumatera is one of the Working Units of the North Sumatra Regional Police, based on Police Regulation Number 14 of 2018 DITSAMAPTA has a main role and task in terms of fostering and carrying out general police duties (regulation, guarding, escorting, patrolling, handling Tipiring, handling TPTK, security and rescue assistance), crowd control and demonstrations, animal assistance in carrying out tracking, deterrence, providing tactical assistance in carrying out investigative and investigative duties. From these various tasks, DITSAMAPTA has problems in collecting data and placing personnel to carry out their main daily tasks, so that things often occur such as multiple assignments to one personnel, several main tasks are not fulfilled due to errors in reporting the number of personnel in real terms, and other tasks related to the assignment or placement of personnel, this is because DITSAMAPTA in its personnel data collection is still manual, resulting in inaccurate information and confusion in deciding the policies of leaders in the field. Given these problems, a study was conducted to monitor the activities of DITSAMAPTA personnel which aims to provide convenience in finding information on any personnel on duty, standby, not entering the office such as: sick, permits, leave and so on. Monitoring of personnel activities is carried out using a website-based application. The website is a platform to make it easier to find information and facilitate communication. The application applies the UCD (User Centered Design) method where the system can provide more accurate and precise according to user needs.